OP37 The alberta ACCEPT study: the impact of a system-wide advance care policy on communication, care planning and documentation. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - King, S; Ghosh, S; Douglas, M; Brisebois, A; Hall, S; Brenneis, C; Sia, W; Heyland, D; Fassbender, K; Davison, S; Simon, J
Abstract : Background: The ACCEPT survey (Audit of Communication, CarE Planning, and DocumenTation) evaluates the quality of Advance Care Planning (ACP) practice through patient-reported experience measures and ACP documentation audit. We evaluated practice three years post system-wide policy for ACP implementation and patient awareness of their "Goals of Care Designation" (GCD) medical order. Method: Consecutive, consenting patients over 55 years with serious, chronic illness or age >80 years with any acute admission were prospectively enrolled from acute medical units in seven hospitals across Alberta, Canada. Research assistants administered the ACCEPT survey within 5 days of admission and reviewed participant charts for ACP and GCD documentation. Results: Of 502 patients (mean age 81 years, 53% female) 93% had a GCD order in their chart but only 30% were aware of this. 33% reported having discussed none of the five key elements of goals of care conversations (patients' values and beliefs, prognosis, patients' fears and concerns, treatment preferences and prior ACP documentation or conversations) with a hospital clinician. Raw agreement between patients' expressed preferences for EOL care and documentation in patient charts was 56% (concordance kappa=0.273). Multivariate regression analysis found that awareness of GCD order was associated with health region, patient frailty, quality of goals of care conversations in hospital and whether ACP conversations were considered important to the patient. Conclusions: Despite a system-wide policy, we found evidence of serious concerns about the quality of ACP and GCD practice. Intentional quality improvement interventions are likely needed to enhance practice and achieve patient-centred care.